Hybrid electricvehiclesandtheirchallenges:Areview - Hannan, MA; Azidin, FA; Mohamed, Azah (Elsevier, 2014)
There arenumbersofalternativeenergyresourcesbeingstudiedforhybridvehiclesaspreparationto replace theexhaustedsupplyofpetroleumworldwide.Theuseoffossilfuelinthevehiclesisarising concern duetoitsharmfulenvironmentaleffects.Amongothersourcesbattery,fuelcell(FC),super capacitors (SC)andphotovoltaiccelli.e.solararestudiedforvehicleapplication.Combinationsofthese sources ofrenewableenergiescanbeappliedforhybridelectricvehicle(HEV)fornextgenerationof transportation. VariousaspectsandtechniquesofHEVfromenergymanagementsystem(EMS),power conditioning andpropulsionsystemareexploredinthispaper.Otherrelated fields ofHEVsuchasDC machine andvehiclesystemarealsoincluded.Varioustypemodelsandalgorithmsderivedfrom simulation andexperimentareexplainedindetails.TheperformancesofthevariouscombinationofHEV systemaresummarizedinthetablealongwithrelevantreferences.Thispaperprovidescomprehensive surveyofhybridelectricvehicleontheirsourcecombination,models,energymanagementsystem(EMS) etc. developedbyvariousresearchers.Fromtherigorousreview,itisobservedthattheexisting technologies moreorlesscancapabletoperformHEVwell;however,thereliabilityandtheintelligent systemsarestillnotuptothemark.Accordingly,thisreviewhavebeenlightedmanyfactors,challenges and problemssustainablenextgenerationhybridvehicle.